The Effect of Oral Nutritional Formula With Three Different Proteins on Type 2 Diabetes Mellitus in vivo - Jia, Ye; Leng, Yue; Cruz, Aliannys Lazára Puente; Bao, Chun Ling; Bao, Bin; Wu, Wenhui; Wang, Peipei; Ma, Ming (Frontiers in Nutrition, 2021)
Oral nutritional (ON) products are an effective way to treat patients with type 2 diabetes mellitus (T2DM) whose gastrointestinal functions are normal. The influence of ON formula prepared with three different proteins on T2DM was studied. The hyperglycaemic mouse model using a high-fat diet (HFD) combined with an intraperitoneal injection of streptozotocin (STZ) was used to simulate T2DM. The study was done for 15 weeks using seven groups of mice: control group (CG, normal mice, and normal food), non-treated group (BG, diabetic mice, and normal food), positive control group (PG, diabetic mice, and HFD), soybean protein group (SPG, diabetic mice, and HFD), silkworm pupa protein group (SPPG, diabetic mice, and HFD), whey protein group (LPG, diabetic mice, and HFD), and whey protein combined with silkworm pupa protein group (LCSSPG, diabetic mice, and HFD). The plasma levels of total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) were analyzed on weeks 2, 10, 12, 14, and 15. The concentration of total protein (TP) and albumin (ALB) of the plasma was increased in SPG, SPPG, and PG comparing with BG (p < 0.05). The TC, TG, and LDL-C levels were decreased, and HDL-C level was increased in SPG, PG, SPPG, PG comparing with BG (p < 0.05). Blood glucose (BLG) levels were decreased 47, 34, 24, and 21% in SPG, LCSSPG, SPPG, and PG, respectively. While BLG was not significantly changed (p ≥ 0.05) in LG after 5 weeks of treatment. Overall, the data suggested that consumption of SP, SPP, LCSSPG Oral-formula may be beneficial for the treatment of T2DM.